2012
DOI: 10.1038/nn.3178
|View full text |Cite
|
Sign up to set email alerts
|

Alzheimer amyloid-β oligomer bound to postsynaptic prion protein activates Fyn to impair neurons

Abstract: SUMMARY Amyloid-beta (Aβ) oligomers are thought to trigger Alzheimer’s disease (AD) pathophysiology. Cellular Prion Protein (PrPC) selectively binds oligomeric Aβ and can mediate AD-related phenotypes. Here, we examined the specificity, distribution and signaling from Aβ/PrP complexes, seeking to explain how they might alter the function of NMDA receptors in neurons. PrPC is enriched in post-synaptic densities, and Aβ/PrPC interaction leads to Fyn kinase activation. Soluble Aβ assemblies derived from human AD … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

25
721
4

Year Published

2013
2013
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 583 publications
(750 citation statements)
references
References 52 publications
25
721
4
Order By: Relevance
“…The concept for repositioning of this agent was based on scientific discoveries that demonstrated that phosphorylation of Fyn tyrosine kinase is related to Aβ-and tau-associated synaptic dysfunction, as well as memory impairments in mouse models of AD [138][139][140].…”
Section: Private-public Partnership For Drug Repositioningmentioning
confidence: 99%
“…The concept for repositioning of this agent was based on scientific discoveries that demonstrated that phosphorylation of Fyn tyrosine kinase is related to Aβ-and tau-associated synaptic dysfunction, as well as memory impairments in mouse models of AD [138][139][140].…”
Section: Private-public Partnership For Drug Repositioningmentioning
confidence: 99%
“…14 In contrast, some studies indicate that PrP C is not required for Aβ oligomer-induced cognitive impairment since the PrP C expressing and knockout mice have no difference in Aβ oligomer-induced synaptic depression, spine density loss, and deficiency of long-term potentiation. 15 Two intracerebroventricular injections of Aβ oligomers to wild-type or PrP C null mice have suggested no PrP C effect on Aβ oligomer-induced memory dysfunction, 10 and modulation of PrP C in AD transgenic mouse models shows no effect on the impairment of the hippocampal synaptic plasticity.…”
mentioning
confidence: 99%
“…13 Aβ oligomer binding to PrP C results in Fyn activation, which leads to phosphorylation of the NR2B subunit of NMDARs. 14 Four replicas were performed. The mock group was used for normalization.…”
mentioning
confidence: 99%
“…14 The toxicity of small soluble Ab species has been proposed to depend on the interaction with specific neuronal proteins, such as the NMDA receptor 15 or the prion protein (PrP C ), 16 which modulates NMDA receptors through Fyn kinase. 17 Alternatively, soluble Ab oligomers may damage neurons by binding to multiple membrane components, including lipids, thereby changing membrane permeability and causing calcium ion leakage into the cell. 5,18 Neuroinflammation arguably has a role in promoting neurotoxicity of Ab plaques.…”
mentioning
confidence: 99%